2014
DOI: 10.4236/ojn.2014.47050
|View full text |Cite
|
Sign up to set email alerts
|

The Direction of Research on Active Aging and Healthy Life Expectancy in Japan

Abstract: In Japan, 18.1% of the population known as baby-boomers will become the late-stage elderly in 2025, thereby needing a foundation to support this change. The Japanese Ministry of Health, Labour and Welfare is promoting the development of a regional comprehensive system allowing the elderly to continue living in their familiar surroundings. However, a care shortage is inevitable unless elders are able to age in good health, regardless of the system's level of enhancement. This study aims to review the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As reported by the ex-servicemen in this study, continued participation in social, economic, cultural, emotional, and civil matters to achieve "Active Ageing" (Tokushige et al, 2014;WHO 2002), may be limited owing to hostile environments. However, ex-servicemen have access to social relationships with marriage partners, members of religious institutions and formal association such as the Legion.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…As reported by the ex-servicemen in this study, continued participation in social, economic, cultural, emotional, and civil matters to achieve "Active Ageing" (Tokushige et al, 2014;WHO 2002), may be limited owing to hostile environments. However, ex-servicemen have access to social relationships with marriage partners, members of religious institutions and formal association such as the Legion.…”
Section: Discussionmentioning
confidence: 77%
“…Overall, the survey found that most people believe that governments should be responsible for the care of their older populations. Globally, debates that surround the ageing issues have agitated for 'active ageing' (Tokushige, Araki, Zusuki, Iwasaki and Ozawa, 2014), which is considered the process of enhancing the quality of life as people age (WHO, 2002). "Activeness" concerns the continued participation in social, economic, cultural, emotional, and civil matters, and not solely being physically active (WHO, 2002;Tokushige et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health means the old group maintains ability to keep health on body and mentality. Thus, they can constantly adapt to social change [8]. Participation means the old group joins the social development positively and promote the social development initiatively [9].…”
Section: The Model Of Active Agingmentioning
confidence: 99%